Title: “Rosettenville community members’ perceptions about the effects of substance abuse on their community - Philani, Khumalo (My University, 2017)
Substance abuse in the Rosettenville community is a big problem and there has been a lot in this area that has been written in the media over the past six months about the substance abuse, as community members protested and burnt down houses of drug dealers in the community. The purpose of this study is to explore the perceptions of key community members in Rosettenville community about the effects of substance abuse in their community. This study utilized the qualitative research to gather information. The type of qualitative design that was utilized in this study was a case study design carried out in Rosettenville community. The is study is an exploratory study as the researcher explored the perceptions of Rosettenville key community members about the effects of substance abuse in their community. A structured interview schedule was used as the instrument for data collection as the researcher used structured questions that allowed participants to elaborate on the answer. The researcher used face-to-face interviews as a method of data collection. Findings were analyzed using thematic analysis. The target population of the study included the staff members from South African National Council on Alcoholism (SANCA Rosettenville) and Community Policing Forum members from the Rosettenville community. The researcher used purposive sampling and the sample size of the study was 10; it was five Community Policing Forum members and five SANCA staff members (SANCA Rosettenville) to get professional opinions about the effects of substance abuse based on their experience in working with substance users in Rosettenville community. The findings of the study highlighted various effects of substance abuse in the community which has affected children, families and individuals. The findings indicated that there are drugs that are universal in the community which affect almost everyone in the community whether using the substance or not. Key Words: Substance abuse, Rosettenville, effects, key community members, families, individual, Government resources, children., drugs, SANCA.
A Research report on a study project presented to Submitted to The Department of Social Work, School of Human and Development, University of Witwatersrand In partial fulfilment of requirement for the degree for Bachelor of Social work